Blockade of maternal anti-HPA-1a-mediated platelet clearance by an HPA-1a epitope-specific F(ab′)(2) in an in vivo mouse model of alloimmune thrombocytopenia - Bakchoul, Tamam (2008)
BACKGROUND: Neonatal alloimmune thrombocytopenia (NAIT) is most commonly caused by transplacental passage of maternal human platelet-specific alloantigen (HPA)-1a antibodies that bind to fetal platelets (PLTs) and mediate their clearance. SZ21, a monoclonal antibody (MoAb) directed against PLT glycoprotein IIIa, competitively inhibits the binding of anti-HPA-1a alloantibodies to PLTs in vitro. The purpose of this investigation was to determine whether SZ21 F(ab′)(2) fragments might be therapeutically effective in inhibiting or displacing maternal HPA-1a antibodies from the fetal PLT surface and preventing their clearance from circulation. STUDY DESIGN AND METHODS: Resting human PLTs from HPA-1ab heterozygous donors were injected into nonobese diabetic/severe combined immunodefi-cient (NOD/SCID) mice. Purified F(ab′)(2) fragments of SZ21 or control immunoglobulin G (IgG) were injected intraperitoneally 30 minutes before introduction of HPA-1a antibodies. Blood samples were taken periodically and analyzed by flow cytometry to determine the percentage of circulating human PLTs. RESULTS: Anti-HPA-1a IgG from NAIT cases were able to efficiently clear HPA-1a–positive PLTs from murine circulation. Administration of SZ21 F(ab′)(2) fragments not only inhibited binding of HPA-1a antibodies to circulating human PLTs, preventing their clearance, but also displaced bound HPA-1a antibodies from the PLT surface. CONCLUSION: F(ab′)(2) fragments of HPA-1a–selective MoAb SZ21 effectively inhibit anti-HPA-1a–mediated clearance of human PLT circulating in an in vivo NOD/SCID mouse model. These results suggest that agents that inhibit binding of anti-HPA-1a to PLTs may have therapeutic potential in the treatment of NAIT.